👤

Bonjour,qui peut m'aider merci
Développer et réduire les expressions suivantes:
a. 6x(5 – 3x) b. (3 – x)(10x + 4) c. 11(- x + 2) – (8x + 7) d. (6 + x) + ( 5x – 4 )( x – 9)


Répondre :

bonjour,

* = multiplier

a. 6x(5 – 3x) =
   6x*5 + 6x*-3x =
   30x-18x² = -18x²+30x

 b. (3 – x)(10x + 4)=
     3*10x + 3*4 -x*10x -x *4 =
   30x+12-10x²-4x =
   -10x²+26x+12

c. 11(- x + 2) – (8x + 7) =
    (11*-x + 11*2)-8x-7 =
   tu finis
   

d. (6 + x) + ( 5x – 4 )( x – 9) =
   6+x+5x*x + 5x*-9 -4*x -4*-9 =
   tu finis

envoies tes résultats, je corrigerais